The Influence of Website-based Education on Adolescent Girls' Behavior Regarding Personal Hygiene During Menstruation - Salsabilah, Putri Naurina; Wulan, Dwi Wahyu; Pratami, Evi; Latip, Abdul (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
This study examines the impact of website-based education on menstrual hygiene practices among teenage girls at SMAS Wachid Hasyim 1 in Surabaya. Out of 8,092 women in Surabaya who had cervical and breast exams in 2020, 5 (0.06%) were suspected of having cancer, and 21 (0.26%) had tumors or lumps. The research aimed to assess how a website could influence menstrual hygiene behavior in teenage girls.The researches used a pretest-posttest design with a one-group sample of 50 respondents, selected randomly from a population of 86 teenage girls. The independent variable was the educational website, and the dependent variable was the girls’ actions regarding personal hygiene during menstruation. Data were collected using a questionnaire between February and March 2024 and analyzed using the Wilcoxon Signed Rank Test, with α < 0.05.The results showed a significant improvement in knowledge, attitudes, and behaviors after the website intervention, with a p-value of 0.000, confirming the effectiveness of the website. In conclusion, the findings suggest that website-based education can positively impact teenage girls' knowledge, attitudes, and behaviors toward menstrual hygiene at SMAS Wachid Hasyim 1 in Surabaya.